A História a contrapelo: ensaio sobre teoria da História em Walter Benjamin - Souza Neto, Manoel Gustavo de (2015)
This study runs on Benjamin`s concept of history, or, more specifically, on his theory of history taken as the reflection on the limits and possibilities of the historical knowledge. It`s an essay which takes his for from Benjamin`s concept of a “dialetical image”, that`s why it`s divided in two parts, leading which one to some of Benjamin`s thought phases: if in a first moment i put my attention in the relations between philosophy of language and theory of knowledge in Benjamin`s preface to the Trauerspielbuch its because it´s in this context that Benjamin will develop his first concept to theory and methodology of history: the concept of origin. In the second essay, which must be fought as a superposition to the firs essay, in a way they the contrast between the two texts, bring to light the differences and continuities between both phases of Benjamin`s work, I focus on Benjamin`s concept of cultural history, with the aim of show how this concept forms the ground to a critic of culture, which means: a critic of the concept of tradition and its linear history, guided by the concept of progress.